Policy recommendations for SEP Licensing under FRAND terms – Interpretation of Huawei Technologies v. ZTE - Söderholm, Camilla (My University, 2020)
As our world is increasingly developing technological elements, it is imperative to develop legal fundamentals in conjunction to such aspects. Patents are a natural part of technology and especially concerning licensing thereof. Disputes are additionally a natural part of patent licensing, due to several ambiguous terms and definitions that lies within the scope of patent law. Therefore, the thesis examines Standard Essential Patent (SEP) licensing under Fair, Reasonable and Non-Discriminatory (FRAND) terms. Additionally, the thesis undertakes an analysis of EU’s competition law principles, Article 102 Treaty of the Functioning of the European Union (TFEU), due to its harmonious effect within SEP licensing. The aim of the thesis is to define the different interpretations of the scope of the term ‘FRAND’ and to provide policy recommendations thereof. The thesis follows a legal-dogmatic research method as a means to identify, systematize, interpret and analyze existing laws, principles, doctrines, international agreements and case law as they are written. In addition, to legal dogmatism, the thesis shall use comparative law, for the analyzation of what ought to change within the European patent system, by comparing European case law. The thesis shall especially compare German and United Kingdom’s case law, by focusing on ECJ’s ruling in Huawei v. ZTE. The thesis obtains an analysis with the purpose of identifying both the visible and hidden issues relating to SEP licensing and FRAND-encumbrances i.e. definition of the scope of the term FRAND. Furthermore, by analyzing the definition, the thesis succeeds in identifying such issues. The analysis is being strengthen by policy recommendations aiming at providing advice to the aforementioned issues – the recommendations given are limited to the European Union and suggest on what ought to be done in order for the current issues to diminish and may aid future scholars to create a de lege ferenda analysis based on the recommendations hereunder.

Maailma muuttuu ja kehittyy jatkuvasti, minkä takia olennaiset lait on oltava vuorovaikutuksessa digitalisoinnin tuomiin muutoksiin. Patentit ovat tavanomaisia elementtejä teknologiassa, ja erityisesti lisensoinnissa. Kiistat sekä niihin liittyvät riidanratkaisut ovat välttämättömiä osia patenttilisensoinnissa epämääräisten määritelmien sekä epäjohdonmukaisten tulkkauksien takia. Siitä syystä opinnäytetyö tutkii Standard Essential Patent (SEP) lisensointia Fair, Reasonable and Non-Discriminatory (FRAND) ehtojen mukaan. Lisäksi, opinnäytetyö analysoi Euroopan Unionin kilpailuoikeus rajoituksia, Artikla 102 Sopimus Euroopan Unionin toiminnasta (SEUT), sillä kilpailuoikeudella on laaja vaikutus SEP lisensointiin. Opinnäytetyön tavoite on todeta ja analysoida ongelmat, jotka ilmaantuvat SEP lisensioinnista Euroopassa, jotta työ pystyy toimittamaan menettelytapa suosituksia kyseisiin oleviin ongelmiin. Opinnäytetyö seuraa eritoten oikeusdogmaattista tutkimusmenetelmää, jonka tarkoitus on identifioida, systemoida, tulkita sekä analysoida voimassaolevaa lainsäädäntöä, kansainvälisiä sopimuksia sekä oikeuskäytäntöä, niin kuin ne ovat kirjoitettu. Oikeusdogmatiikan lisäksi, opinnäytetyö käyttää lainsäädäntöjen sekä oikeuskäytäntöjen vertailevaa tutkimusta löytääkseen menettelytapasuosituksia. Opinnäytetyö tutkii erityisesti Saksan sekä Iso-Britannian oikeuskäytäntöä, keskittyen eritoten Euroopan tuomioistuimen Huawei v. ZTE päätökseen. Opinnäytetyö suorittaa analyysin, joka tuo esiin olennaiset näkyvissä olevat sekä kätketyt ongelmat koskien SEP lisensointia, erityisesti ongelmia koskien FRAND termin tulkintaa. Analysoinnin myötä, edellä mainitut ongelmat esiintyvät selkeästi. Ongelmien havaitsemisen lisäksi, opinnäytetyö toimittaa mainittuihin ongelmiin suosituksia, jotka SEP lisensoinnin osapuolet, ja eritoten Euroopan Unionin, pitäisi ottaa huomioon. Nämä suositukset selventävät sitä mitä tulisi tehdä, jotta nykypäivän ongelmat vähenisivät, jonka lisäksi suositukset voivat auttaa tulevia tutkijoita kehittämään de lege ferenda analyysin.
Keywords: EU, FRAND, IP, Licensing, Patent, SEP, technology, TFEU